Crosstalk Between Senescent Bone Cells and the Bone Tissue Microenvironment Influences Bone Fragility During Chronological Age and in Diabetes - Teissier, Thibault; Temkin, Vladislav; Pollak, Rivka Dresner; Cox, Lynne S. (Frontiers in Physiology, 2022)
Bone is a complex organ serving roles in skeletal support and movement, and is a source of blood cells including adaptive and innate immune cells. Structural and functional integrity is maintained through a balance between bone synthesis and bone degradation, dependent in part on mechanical loading but also on signalling and influences of the tissue microenvironment. Bone structure and the extracellular bone milieu change with age, predisposing to osteoporosis and increased fracture risk, and this is exacerbated in patients with diabetes. Such changes can include loss of bone mineral density, deterioration in micro-architecture, as well as decreased bone flexibility, through alteration of proteinaceous bone support structures, and accumulation of senescent cells. Senescence is a state of proliferation arrest accompanied by marked morphological and metabolic changes. It is driven by cellular stress and serves an important acute tumour suppressive mechanism when followed by immune-mediated senescent cell clearance. However, ageing and pathological conditions including diabetes are associated with accumulation of senescent cells that generate a pro-inflammatory and tissue-destructive secretome (the SASP). The SASP impinges on the tissue microenvironment with detrimental local and systemic consequences; senescent cells are thought to contribute to the multimorbidity associated with advanced chronological age. Here, we assess factors that promote bone fragility, in the context both of chronological ageing and accelerated ageing in progeroid syndromes and in diabetes, including senescence-dependent alterations in the bone tissue microenvironment, and glycation changes to the tissue microenvironment that stimulate RAGE signalling, a process that is accelerated in diabetic patients. Finally, we discuss therapeutic interventions targeting RAGE signalling and cell senescence that show promise in improving bone health in older people and those living with diabetes.